Analisis Kebijakan Publik: Proses Legislasi dan Implementasi Perda Kota Pariaman Nomor 29 Tahun 2023 tentang Tata Cara Pelaksanaan PPDB - Ativa Mardatila (CV. ITTC INDONESIA, 2025)
This article examines the legislative process and implementation of the Pariaman City Regional Regulation (Perda) No. 29 of 2023 concerning Procedures for Implementing the Admission of New Learners (PPDB). This regulation aims to realize objective, transparent, accountable, and non-discriminatory PPDB in Pariaman City. Through a case study approach, this article analyzes the stages from issue identification to policy implementation. The findings show that the success of legislation is influenced by public participation, political support, and inter-institutional coordination. The article recommends strengthening the monitoring system and improving socialization to ensure effective implementation.